REPRESENTASI BUDAYA VISUAL KARYA SENI RUPA KONTEMPORER PUTU SUTAWIJAYA, 1998 - 2010 - Muhammad Wasith Albar (Fakultas Ilmu Budaya universitas Hasanuddin, 2017)
This paper is a study of the representation of multiculturalism and globalization in seven contemporary art works of Putu Sutawijaya between 1998 an d0201 as a creative journey and process of the contemporary artist through his visual cultural ideas from his exhibition at the National Galery in Jakarta (Legacy of Sagacity, 20—30 November 2008) and one sculpture (Merasa Bebas) in the Art Apreciation Park in the Faculty of Culture at Universitas Indonesia in Depok (2010). Through preliminary study visual culture of the seven contemporary works which are diverse and dynamics can be discovered that Putu Sutawijay always maintain a consistent concept and full authority in his creative process where “Idea is Form” in passing his message. This paper is expected will be able to recognize various multicutural interpretation and globalization through the seven contemporary art works by Putu Sutawijaya as an artis who resides in two cultural regions—Bali and Yogyakart, as ide of his participation in residency programs in Switzerland and Malaysia.